TI_GERICHTE 16.2017.9 vom 22. März 2019 , Compravendita mobiliare - mora -inadempimento contrattuale - recesso dal contratto - TI Tribunale d'appello (2019)
Compravendita mobiliare - mora -inadempimento contrattuale - recesso dal contratto